On y-closed Rickart Modules - Al-Bahrani , Bahar hamad; Rahman, Mohammed Qader (Iraqi Journal of Science, 2020)
In a previous work, Ali and Ghawi studied closed Rickart modules. The main purpose of this paper is to define and study the properties of y-closed Rickart modules .We prove that, Let and be two -modules such that is singular. Then is -y-closed Rickart module if and only if Also, we study the direct sum of y-closed Rickart modules.